East
CentricArch
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
WinterTravelstead
Apr 9, 2018, 1:33:40 AM
16
Simplify p(p - q) - q(q - p).
+1
(
1
) Answers
Ryiann
Apr 9, 2018, 6:44:21 AM
p^2-q^2 because p(p - q) - q(q - p) = p^2 - pq - q^2 + pq = p^2 - q^2
Add answer
Sign in
Sign up
Related Questions
Simplify p(p - q) - q(q - p).
simplify 7(n - p) 5p. user: simplify p(p - q) - q(q - p).
Subtract And Simplify. (4p²q-pq²+q³) - (3p²q+2pq²-q³) A. p²q-3pq²+2q³ B. p²q-2pq² C. p²q-3pq...
If p and q are nonzero integers, which pair of points must lie in the same quadrant? (p, q) and ...
S = p/(q + p(1 − q)) solve for q
P(Q)= 0.18 P(R)= 0.2 Find P(Q or R)
p varies directly as q; p=6 when q=120. find p when q is 100
solve for p. 3(p+q)=p a. q= -2/3p b. q= -3/2p c. p= -2/3q d. p= -3/2q
Which statement is the Law of Detachment? (1 point) If p q is a true statement and q is true, th...
P is inversely proportional to Q. When P=100, Q=32 Write an equation connecting P and Q